Laju Dekomposisi dan Pelepasan Hara dari Serasah pada Dua Sub-Tipe Hutan Rawa Gambut di Kalimantan Tengah - Sulistiyanto Y; Rieley JO; Limin SH (Jurnal Manajemen Hutan Tropika, 2005)
Decomposition processes of litter in peat swamp forest in the upper catchment of the Sebangau River in Central Kalimantan, Indonesia were studied. Litterbags were sampled every six months from November 2000 to May 2002 and analyzed for total content of N, P, K, dan Ca. Litterbags was collected in three permanent study plots, 50 x 50 m, which were established in mixed swamp forest (MSF) and low pole forest (LPF). In each plot, 25 litterbags (25 sub-plot) were placed in forest floor. Every six months 12 litterbag samples were harvested from the study plots (MSF and LPF) and these were air dried, oven dried and weighed. Six litterbag samples were taken from hollows and other six samples from hummocks. Weight loss in both sub-tipe of forest, mixed swamp forest and low pole forest was fast in the first six months. Potassium was the fastest nutrient loss in the mixed swamp forest and low pole forest. Decomposition rate (k) in the mixed swamp forest and low pole forest are 0.396 yr -1 and 0.285 yr -1 respectively.